Q: Simplify by combining like-terms x – 10x + 8x

A:
x – 10x + 8x
= -9x + 8x
= -x

OxTornado007|Points 4958|

Expert answered|eturker|Points 2415|

Question

Asked 7/16/2012 12:48:00 PM

Updated 8/16/2014 3:47:38 PM

1 Answer/Comment

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [8/16/2014 3:47:28 PM], Confirmed by andrewpallarca [8/16/2014 3:47:30 PM]

Rating

3

1x - 10x = -9x

Added 8/16/2014 3:47:38 PM

This answer has been confirmed as correct and helpful.

Simplify by combining like terms 16xy^3 – 21xy^3 + 7xy^3 **Weegy:** First you get rid of the negative sign on -5y on both sides, leaving you with 5y-9 = y-1. Subtract the y on the right side ad you end up with 4y-9 =1. Add the 9 to the right side and your answer is 4y=10. (More)

Question

Expert Answered

Updated 8/16/2014 3:48:33 PM

1 Answer/Comment

16xy^3 – 21xy^3 + 7xy^3

= 16xy^3 - 14xy^3

= 2xy^3

= 16xy^3 - 14xy^3

= 2xy^3

Added 8/16/2014 3:48:32 PM

This answer has been confirmed as correct and helpful.

Solve using PEMDAS -12 – 48 ÷ 6 x 9^2 + 10 **Weegy:** -626 (More)

Question

Expert Answered

Updated 6/2/2014 11:59:22 AM

1 Answer/Comment

-12 – 48 ÷ 6 x 9^2 + 10;

-12 - 48 ÷ 6 x 81 + 10;

-12 - 8 x 81 + 10;

-12 - 648 + 10;

-12 - 638 = -650

-12 - 48 ÷ 6 x 81 + 10;

-12 - 8 x 81 + 10;

-12 - 648 + 10;

-12 - 638 = -650

Added 6/2/2014 11:59:21 AM

This answer has been confirmed as correct and helpful.

26,996,076 questions answered

There are no comments.